Chapter La professionalizzazione del coordinatore dei servizi alla persona. Quale ruolo nel mondo del lavoro? - DADDI, DEBORA (Studies on Adult Learning and Education, 2022)
In view of the increasing number of social enterprises in recent years, the European Commission (2020) has undertaken a mapping study (2014-2020) of social ecosystems in order to understand their evolution, activities, and professional profiles. In Italy, workers in social enterprises account for 53% (ISTAT 2020) of the majority of which consist of/include workers in the social and care services. It is specifically within these services that the «value of knowledge and skills that are not only specifically technical-professional but also strategic and transversal, cognitive and metacognitive, reflective» (Epifani 2003, 23) is becoming increasingly important, in line with the current indications of the European Skills Agenda (European Commission 2021). This phenomenon concerns even more particularly the intermediate functions, i.e. those support positions, which in part hold management and coordination functions (Abhervé and Dubois 2009). In light of this framework, this study investigates the figure of the personal services coordinator, i.e. a second-level professional who, working both in the educational and in the managerial, combines his actions between very different areas of competence.